IMPACT OF CURRICULUM MANAGEMENT ON SCIENCE ACHIEVEMENT IN INCLUSIVE PRIMARY SCHOOLS IN EAST JAVA: LEARNING MOTIVATION AS MEDIATOR - Martha Mahendra, Angga; Ustradi Osijo, Immanuel; Ibadil Maula, Farij; Erni Munikasari, Lavita (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2024)
Phenomenon/Issue: The study explores the effectiveness of culture management curriculum grading in improving student performance in inclusive elementary schools, particularly in science classes. Purpose: It aims to examine the impact of a multilevel culture management curriculum on student performance, with learning motivation as a mediating factor. Novelty: The study uniquely incorporates learning motivation as a mediator within the curriculum culture management framework, offering new insights for inclusive elementary education. Research Methods : Using a quantitative approach, data is collected from 314 inclusive elementary school students in East Java through questionnaires. Structural Equation Modeling (SEM) and mediation analysis examine the relationships among curriculum management, motivation, and academic achievement. Results: Expected findings should highlight the importance of a structured, multilevel curriculum in fostering academic success in inclusive settings, especially by boosting student motivation. SEM analysis will reveal the strength and nature of these relationships, with motivation likely playing a significant role in performance improvement. Research Contributions: This research advances theoretical understanding of curriculum culture management in inclusive education and provides a practical framework for motivation-centered strategies to enhance student performance. The findings may serve as a guide for policymakers and educators in designing curricula that address both academic and motivational needs in inclusive settings.